Effects of Ketogenic Dieting on Body Composition, Strength, Power, and Hormonal Profiles in Resistance Training Men. Issue 12 (December 2020) - Wilson, Jacob M.; Lowery, Ryan P.; Roberts, Michael D.; Sharp, Matthew H.; Joy, Jordan M.; Shields, Kevin A.; Partl, Jeremy M.; Volek, Jeff S.; D'Agostino, Dominic P.
Abstract : Abstract: Wilson, JM, Lowery, RP, Roberts, MD, Sharp, MH, Joy, JM, Shields, KA, Partl, JM, Volek, JS, and D'Agostino, DP. Effects of ketogenic dieting on body composition, strength, power, and hormonal profiles in resistance training men. J Strength Cond Res 34(12): 3463–3474, 2020—This study investigated the impact of an isocaloric and isonitrogenous ketogenic diet (KD) versus a traditional western diet (WD) on changes in body composition, performance, blood lipids, and hormonal profiles in resistance-trained athletes. Twenty-five college-aged men were divided into a KD or traditional WD from weeks 1 to 10, with a reintroduction of carbohydrates from weeks 10 to 11, while participating in a resistance training program. Body composition, strength, power, and blood lipid profiles were determined at weeks 0, 10, and 11. A comprehensive metabolic panel and testosterone levels were also measured at weeks 0 and 11. Lean body mass (LBM) increased in both the KD and WD groups (2.4% and 4.4%, p < 0.01) at week 10. However, only the KD group showed an increase in LBM between weeks 10 and 11 (4.8%, p < 0.0001). Finally, fat mass decreased in both the KD (−2.2 ± 1.2 kg) and WD groups (−1.5 ± 1.6 kg). Strength and power increased to the same extent in the WD and KD conditions from weeks 1 to 11. No changes in any serum lipid measures occurred from weeks 1 to 10; however, a rapid reintroduction of carbohydrate from weeks 10 to 11 raised plasma triglyceride levels in the KD group. Total testosterone increased significantly from weeks 0 to 11 in the KD diet (118 ng·dl −1 ) as compared to the WD (−36 ng·dl −1 ) from pre to post while insulin did not change. The KD can be used in combination with resistance training to cause favorable changes in body composition, performance, and hormonal profiles in resistance-trained men.